Professional Identity and Self-efficacy Among Occupational Therapy Students Engaged in Objective Structured Clinical Examination Utilizing Simulation Learning - Hassan Izzeddin Sarsak PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Objective structured clinical examination (OSCE) is widely used in health programs and has been applied in medical education to enhance clinical knowledge and help build clinical competence and confidence. It is carried out in different clinical stations that simulate real clinical situations and scenarios and helps prepare students for clinical training and practical applications. The purpose of this study was to investigate the change in professional identity and self-efficacy of occupational therapy students after applying OSCE utilizing simulated learning. A pre-post study design was used. The participants were 48 occupational therapy university students at 1 university in Saudi Arabia. Total scores and subscale scores for professional identity and self-efficacy were compared before and after OSCE using the Wilcoxon signed- rank test. Spearman's rank correlation coefficient was calculated to examine the relationship between professional identity and self-efficacy. There were significant increases in both professional identity and self-efficacy total scores after OSCE ( P  < .05). Most items in the professional identity, such as choosing occupational therapy again ( P  < .01) and improving occupational therapy skills ( P  < .01) and the self-efficacy, such as doing very well in class ( P  < .01) and ability to learn the material for class ( P  < .01) increased significantly. OSCE utilizing simulated-based learning plays a supportive role in forming occupational therapy students’ identities as clinicians and can potentially enhance their overall self-efficacy, professional identity and growth. It is a beneficial teaching and learning strategy for occupational therapy educators and considered important steppingstones for students transitioning to real life occupational therapy practice.